Advances in Wheat Physiology in Response to Drought and the Role of Plant Growth Promoting Rhizobacteria to Trigger Drought Tolerance - Manon Camaille; Nicolas Fabre; Christophe Clément; Essaid Ait Barka (Microorganisms, 2021)
In the coming century, climate change and the increasing human population are likely leading agriculture to face multiple challenges. Agricultural production has to increase while preserving natural resources and protecting the environment. Drought is one of the major abiotic problems, which limits the growth and productivity of crops and impacts 1–3% of all land.To cope with unfavorable water-deficit conditions, plants use through sophisticated and complex mechanisms that help to perceive the stress signal and enable optimal crop yield are required. Among crop production, wheat is estimated to feed about one-fifth of humanity, but faces more and more drought stress periods, partially due to climate change. Plant growth promoting rhizobacteria are a promising and interesting way to develop productive and sustainable agriculture despite environmental stress. The current review focuses on drought stress effects on wheat and how plant growth-promoting rhizobacteria trigger drought stress tolerance of wheat by highlighting several mechanisms. These bacteria can lead to better growth and higher yield through the production of phytohormones, osmolytes, antioxidants, volatile compounds, exopolysaccharides and 1-aminocyclopropane-1-carboxylate deaminase. Based on the available literature, we provide a comprehensive review of mechanisms involved in drought resilience and how bacteria may alleviate this constraint